A polycarbonate modified material for 3D printing and a preparation method thereof, and a test method for 3D printing filaments and interlayer strength
By adding aliphatic aromatic copolyester and epoxy polyester chain extender to the 3D printing material, the interlayer bonding strength of the polycarbonate material is improved, and a test method is proposed to solve the interlayer bonding of the 3D printing material. The problem of low junction strength achieves high strength and transparency of the material.
Patent Information
- Application Number
- CN202011155932.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-10-26
AI Technical Summary
The bonding strength between layers of 3D printing materials is low, resulting in the easily damaged product structure and lack of effective testing methods to characterize interlayer strength.
By adding aliphatic aromatic copolyester and epoxy polyester chain extender to the polycarbonate material, the bonding strength between layers is improved, and a kind of layer strength is proposed for testing the 3D printed polycarbonate modified material. The method includes printing the material into sheets, measuring tensile breaking forces and real bond widths to calculate interlayer strength.
Improve the interlayer bonding strength of 3D printing materials, making the product less likely to break, and provides an intuitive test method to reflect the interlayer bonding conditions, ensuring that the transparency and strength of the material reach more than 85% of the intrinsic tensile strength. .
Smart Images

Figure CN114507430B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and in particular to a polycarbonate modified material for 3D printing with high interlayer bonding strength, a preparation method thereof, and a testing method for 3D printing filaments and interlayer strength. Background Art
[0002] 3D printing is an emerging processing technology that has developed rapidly in recent years. In addition to industrial production and civilian fields, it is also widely used in aerospace, military, medical and other fields. It is a technology based on digital model files, which finally obtains the required objects by printing layer by layer. Up to now, there are five main process technologies that are the most mature and widely used, including stereolithography (SLA), laminated object manufacturing (LOM), fused deposition modeling (FDM), selective laser sintering (SLS), and selective laser melting (SLM). Among them, fused deposition modeling has the longest development time, the most mature technology, and has been the most widely used.
[0003] The thermoplastic printing plastics commonly used in FDM technology include acrylonitrile-butadiene-styrene copolymer (ABS), polylactic acid (PLA), nylon (PA), high-impact polystyrene (HIPS), polycarbonate (PC), etc. Compared with other printing materials, PC has good transparency, insulation, excellent mechanical properties and thermal stability, and is an engineering material with excellent comprehensive performance. However, in 3D printing, due to the defects of the FDM printing method itself and the high glass transition temperature of PC, the bonding strength between the layers of the printed components is low, and defects are easily generated between the layers.
[0004] In the present invention, the PC material is modified by adding aliphatic aromatic copolyester and epoxy polyester chain extender, so that the bonding strength between layers of the obtained PC modified material is significantly improved. Summary of the invention
[0005] One of the technical problems to be solved by the present invention is to provide a PC modified material, by adding aliphatic aromatic copolyesters and epoxy polyester chain extenders to PC raw materials, so as to improve the problem that the interlayer bonding strength of 3D printing materials is too low and the product structure is easily damaged.
[0006] The second technical problem to be solved by the present invention is to provide a testing method for characterizing the interlayer strength of 3D printed polycarbonate modified materials corresponding to the first technical problem to be solved.
[0007] In order to solve one of the above technical problems, one of the purposes of the present invention is to provide a polycarbonate modified material for 3D printing, which is obtained by blending raw materials comprising the following components, in parts by weight:
[0008] (1) 60 to 90 parts of polycarbonate, preferably 65 to 90 parts of polycarbonate;
[0009] (2) 10 to 40 parts of aliphatic aromatic copolyesters, preferably 10 to 35 parts of aliphatic aromatic copolyesters;
[0010] (3) 0.1 to 1 part of epoxy polyester chain extender, preferably 0.2 to 0.6 part of epoxy polyester chain extender.
[0011] In the above technical solution, the polycarbonate is a high molecular polymer containing carbonate groups in the molecular chain, and is at least one of aliphatic polycarbonate, alicyclic polycarbonate and aromatic polycarbonate, preferably aromatic polycarbonate, and more preferably bisphenol A polycarbonate.
[0012] In the above technical solution, the molecular chain segment of the aliphatic aromatic copolyester contains one or more aliphatic diol units, at least one of aliphatic diacid or aliphatic diacid anhydride, aliphatic diacyl halide, and aliphatic diacyl ester units, and at least one of aromatic diacid or aromatic diacid anhydride, aromatic diacyl halide, and aromatic diacyl ester units.
[0013] In the above technical scheme, the aliphatic aromatic copolyester includes polyethylene terephthalate-co-oxalate, polyethylene terephthalate-co-malonate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-suberate, polyethylene terephthalate-co-oxalate. Ester, poly(propylene terephthalate-co-malonate), poly(propylene terephthalate-co-succinate), poly(propylene terephthalate-co-glutarate), poly(propylene terephthalate-co-adipate), poly(propylene terephthalate-co-suberate), poly(propylene terephthalate-co-sebacate), poly(butylene terephthalate-co-oxalate), poly(butylene terephthalate-co-malonate), Polybutylene terephthalate-co-succinate, polybutylene terephthalate-co-glutarate, polybutylene terephthalate-co-adipate, polybutylene terephthalate-co-suberate, polyhexylene terephthalate-co-oxalate, polyhexylene terephthalate-co-malonate, polyhexylene terephthalate-co-succinate, polyhexylene terephthalate-co-glutarate, poly At least one of poly(hexylene terephthalate-co-adipate), poly(hexylene terephthalate-co-suberate), etc., preferably at least one of poly(butylene terephthalate-co-adipate), poly(ethylene terephthalate-co-adipate), poly(ethylene terephthalate-co-succinate), poly(butylene terephthalate-co-succinate), more preferably poly(butylene terephthalate-co-adipate).
[0014] The aliphatic aromatic copolyesters in the present invention include linear and branched copolyesters. One or more branching agents are added during the synthesis of the branched copolyesters. The branching agent is generally a polyacid with two or more carboxyl groups, a polyol or polyhydroxy acid with two or more hydroxyl groups, etc. Applicable branching agents include glycerol, trimethylolethane, trimethylolpropane, 1,2,4-butanetriol, pentaerythritol, 1,2,6-hexanetriol, sorbitol, 1,2,3-benzenetricarboxylic acid (hemimellitic acid), 1,2,4-benzenetricarboxylic acid (triimellitic acid), 1,3,5-benzenetricarboxylic acid (trimesic acid) and acid anhydrides, etc.
[0015] In the above technical scheme, the epoxy polyester chain extender includes an oligomer containing multiple epoxy groups and having high reactivity, preferably an oligomer containing 5 to 9 epoxy groups, and more preferably an acrylic acid and styrene copolymer containing 6 to 8 epoxy groups or a styrene-methacrylate glycidyl ester copolymer containing 6 to 8 epoxy groups.
[0016] The weight average molecular weight of the epoxy polyester chain extender is 4000-7000, preferably 6000-6800.
[0017] The epoxy polyester chain extender can be specifically produced by BASF ADR-4300, ADR-4370, ADR-4380, ADR-4385, etc.; KL-E4300, KL-E4370, KL-E4370B, etc. produced by Shanxi Chemical Research Institute. More preferably ADR-4300.
[0018] In the above technical solution, the interlaminar strength of the 3D printed strips of the polycarbonate modified material reaches more than 80% of the intrinsic tensile strength of the material, preferably more than 85%.
[0019] The intrinsic tensile strength of the material refers to the strength obtained by stretching the polymer material into a standard sample. In the above technical solution, the intrinsic tensile strength of the material is the tensile strength of the carbonate modified material of the present invention, which is measured by injection molding the carbonate modified material into a standard sample according to GB / T1040-92 standard.
[0020] The polycarbonate modified material for 3D printing of the present invention adopts an epoxy polyester chain extender to improve the interface compatibility between carbonate and polycarbonate, increase the interlayer bonding strength of the printed material, and at the same time improve the transparency of the product.
[0021] The second object of the present invention is to provide a method for preparing the polycarbonate modified material for 3D printing, comprising the following steps: blending and extruding components including the polycarbonate, aliphatic aromatic copolyester, and epoxy polyester chain extender to obtain the polycarbonate modified material.
[0022] In the above technical solution, preferably, the required amounts of polycarbonate, aliphatic aromatic copolyester, and epoxy polyester chain extender are fully mixed in a mixing device, then blended and extruded in a twin-screw extruder, granulated and dried to obtain the polycarbonate modified material for 3D printing.
[0023] In the above technical solution, preferably, the rotation speed of the twin-screw extruder is 50 to 150 rpm; and the extrusion temperature is 210 to 250°C.
[0024] The third object of the present invention is to provide a 3D printing filament prepared from the polycarbonate modified material for 3D printing.
[0025] A fourth object of the present invention is to provide a method for preparing the 3D printing filament, comprising continuously melt-extruding the polycarbonate modified material and obtaining the 3D printing filament by oriented drawing.
[0026] In the above technical solution, preferably, continuous melt extrusion is used to melt and extrude the polycarbonate modified material for 3D printing in a screw extruder, cool it, and then draw it through orientation to obtain the polycarbonate 3D printing wire. Preferably, a single screw extrusion method is used, in which the polycarbonate modified material is melt extruded through a single screw extruder, cooled in two water baths at different temperatures, and then drawn and rolled to obtain the 3D printing wire.
[0027] In the above technical solution, the single-screw continuous extrusion temperature is preferably 210 to 250°C.
[0028] In the above technical solution, the single screw continuous extrusion speed is preferably 12.0 to 14.0 rpm.
[0029] In the above technical solution, the traction frequency of the drafting device is preferably 2.5 to 3.5.
[0030] In order to solve the second technical problem above, the fifth object of the present invention is to provide a method for testing the interlayer strength of a 3D printed product of the polycarbonate modified material for 3D printing, comprising the following steps:
[0031] The sheets printed from the polycarbonate modified material are made into splines, the tensile breaking force is tested, and then the actual bonding width of the sheets is measured. The interlayer strength is calculated according to the formula: interlayer strength = tensile breaking force / (actual bonding width*spline length).
[0032] In the above technical solution, preferably, the polycarbonate modified material is printed into a thin sheet of designed size using a 3D printer (such as a MakerBot Replicator 2X 3D printer). Then, it is cut into strips of corresponding size using a cutter and a punching machine. The tensile breaking force of the strip is tested using a tensile tester. The actual bonding width of the thin sheet is measured using an optical microscope to obtain the actual bonding area, and finally the interlayer strength is calculated.
[0033] Specifically, the sample strip is observed using an optical microscope to obtain the true bonding width, and finally the interlaminar strength = tensile breaking force / (true bonding width*speline length) is obtained.
[0034] In the above technical solution, the number of layers n in the thickness direction of the sheet can be 1 to 4 layers, such as a single layer, a double layer, or a quadruple layer, preferably a single layer sheet.
[0035] In the above technical solution, the thickness h of each printed layer in the height direction of the sheet is 0.1 mm to 0.3 mm, specifically 0.1 mm, 0.2 mm, 0.3 mm, preferably 0.2 mm. The height H of the sheet in the height direction is preferably 30 mm to 70 mm.
[0036] In the above technical solution, the length L of the thin sheet in the longitudinal direction is preferably 200 mm to 300 mm.
[0037] In the above technical solution, the width of the spline is 3 mm to 8 mm, preferably 4 to 6 mm, and the length of the spline is 40 to 60 mm.
[0038] In the above technical solution, the length direction of the spline is the height direction of the sheet, and during the tensile test, the length direction of the spline is the tensile direction.
[0039] In the above technical solution, the tensile speed of the interlaminar strength test is 5 to 50 mm / min, preferably 5 to 20 mm / min.
[0040] In the above technical solution, the magnification of the optical microscope eyepiece is 10-30, preferably 10-20; the magnification of the objective lens is 5-20, preferably 5-10.
[0041] The polycarbonate modified material of the present invention has stronger interlayer bonding strength than other PC printing materials during 3D printing, and the printed product is not easy to break, and the product transparency is better. The present invention also proposes a method for testing interlayer strength, which can intuitively reflect the interlayer bonding condition in 3D printed products. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The DSC data of PC / PBAT / ADR is a heating curve.
[0043] Figure 2 Changes in interlayer strength of PC / PBAT / ADR filaments at different printing layer thicknesses.
[0044] Figure 3 Changes in interlayer strength of PC / PBAT / ADR wires under different formulations.
[0045] Figure 4 Cross-sectional view of PC / PBAT / ADR printed sheet.
[0046] Figure 5 Schematic diagram of the front view of the sheet of the test method for the interlayer adhesion of 3D printing materials.
[0047] Figure 6 Schematic diagram of the left side of the sheet showing the method for testing the interlayer adhesion of 3D printing materials.
[0048] Figure 7 Schematic diagram of the top view of the thin film of the testing method for the interlayer adhesion of 3D printing materials.
[0049] Figure 8 Injection molding spline diagram of 3D printing materials of embodiments and comparative examples.
[0050] from Figure 8 It can be seen that after adding the chain extender ADR, the 3D printing material changes from yellowish to clear, which helps the transparency of the product. DETAILED DESCRIPTION
[0051] The present invention is specifically described by the following examples. It is necessary to point out that the following examples are only for further explanation of the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above invention.
[0052] The present invention performs performance measurement according to the following method:
[0053] Melt flow index (MFR) measurement method: According to ISO 1133 standard, Instron CEAST MF20 melt index meter is used for measurement, barrel temperature is 250°C, weight load is 5kg, die diameter is 2.095mm, length is 8mm, preheating time is 4min, automatic sample cutting is performed at set time intervals, and the average value is calculated for 5 times. The measurement result is expressed in grams per 10 minutes (g / 10min).
[0054] Thermal performance analysis (DSC): The test was carried out on a Discovery series differential scanning calorimeter (DSC) produced by TA Instruments. The processing software was TA Instruments Trios version 3.1.5. The DSC instrument was equipped with a TA Refrigerated Cooling System 90 mechanical refrigeration accessory. The test atmosphere was 50 mL / min of nitrogen, and the sample amount required for the test was 5 to 10 mg. The test procedure is as follows: first stabilize the temperature at 40°C, then increase the temperature to 250°C at 10°C / min and keep the temperature constant for 1 minute to remove the thermal history, then cool down to -50°C at 10°C / min, and then increase the temperature to 250°C at 10°C. Record the cooling process and the second heating process to study the thermal properties of the sample. Through the DSC test, the software can directly derive the glass transition ("T g ”), melting temperature (“T m ”) and other information.
[0055] Tensile strength test: The test was carried out on a universal tester (Model 3344) produced by Instron Corporation of the United States. The test temperature was 20°C, the test humidity was 65%, the stretching rate was 5 mm / min, the effective length of the sample was 30 mm, and the tensile stress of 5 samples in the same batch was recorded and the average value was taken.
[0056] [Example 1]
[0057] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Polybutylene adipate terephthalate (PBAT) is produced by BASF of Germany with the brand name C1200. Epoxy polyester chain extender is produced by BASF, Germany, with the brand name ADR-4300. The two particles were dried in a vacuum oven at 60°C for 5 hours to remove moisture. Then they were mixed in a mixer according to the specific ratios of PC / PBAT / ADR of 90 / 10 / 0.5, 85 / 15 / 0.5, 80 / 20 / 0.5, and 75 / 25 / 0.5 by mass, and the mixing time was 20 minutes. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are: 210°C, 220°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, and 230°C, and the screw speed is set at 100rpm. During stable operation, the torque is 70% of the maximum value. The extruder is equipped with a circular die with a diameter of 3 mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles with a set diameter of about 3 mm by a pelletizer. The above particles are named 10% PBAT, 15% PBAT, 20% PBAT, and 25% PBAT, and then they are dried in a vacuum oven at 60°C for 4 hours and packaged for use.
[0058] [Example 2]
[0059] All the above four particles, as well as the raw materials PC and PBAT, were subjected to differential scanning calorimetry (DSC) tests according to the steps described above. The second heating curve ( Figure 1 The crystallization temperature (“T c ”), melting temperature (“T m ”), glass transition (“T g ”), and other information, the values are listed in Table 1.
[0060] Table 1 Thermal performance parameters of each particle obtained from DSC results.
[0061]
[0062] Polycarbonate modified materials are colorless and transparent. Figure 1 From Table 1, we can see that only one glass transition temperature appears after blending and it is between the glass transition temperatures of PC and PBAT, which confirms that the three components PC, PBAT and ADR have good compatibility, and within the prepared content range, as the PBAT content increases, the glass transition temperature decreases linearly. For example, after adding 20% PBAT to PC, the glass transition temperature of the material decreases from 144.4°C to 90.1°C.
[0063] [Example 3]
[0064] The four kinds of particles obtained in Example 1 and PC raw materials were subjected to melt index measurement in an Instron CEAST MF20 melt index meter. The results are shown in Table 2.
[0065] Table 2 Melt index of various materials at 250℃ and 5kg
[0066]
[0067] From Table 2, we can see that at 250°C and 5kg, with the addition of high-fluidity PBAT, the fluidity of the PC / PBAT / ADR blend gradually increases, and the processability is effectively improved. For example, when the PBAT content is 20 parts, the melt index increases to 28.62g / 10min.
[0068] [Example 4]
[0069] The 3D printing wire was prepared by a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. It consists of a single screw extruder, two water bath cooling structures of hot water bath and cold water bath, and winding parts. A die with a diameter of about 2 mm is configured. The particles prepared in Example 1 are added to the feeder in batches, with about 1.5 kg of sample for each component. The feeder maintains a temperature of 80°C and blast drying. The single screw speed and roller speed are adjusted, and the diameter of the wire is controlled by adjusting the traction speed. The specific parameters are shown in Table 3.
[0070] Table 3 Processing conditions of 3D printing filaments
[0071]
[0072] As shown in Table 3, although the samples with different composition contents have different glass transition temperatures and fluidities, it is necessary to adjust the processing temperature, screw speed, roller speed, etc. to control the filament to about 1.73 mm, so that it can be applied to FDM 3D printing.
[0073] [Example 5]
[0074] The 3D printing filaments 15% PBAT, 20% PBAT, and 25% PBAT prepared in Example 4 were 3D printed on a MakerBot Replicator 2X 3D printer. The sheet parameters and printing parameters are as follows: the sheet size is a rectangle of 300mm×50mm×0.5mm, the printing parameters are high, standard, and low resolution, the nozzle extrusion speed is 90mm / s, the moving speed is 90mm / s, the spline filling rate is 100%, the height of each layer is 100, 200, and 300μm, the nozzle temperature is 240, 245, 250, 255, 260, 265, and 270℃, and the bottom plate temperature is 100℃. Under these conditions, all three samples obtained regular sheets. A tensile spline with a size of 50mm×6mm was prepared using a cutter and a punching machine. Let it stand in a dry environment for use.
[0075] [Example 6]
[0076] The tensile specimens prepared in Example 5 were tested using a universal tester (Model 3344) produced by Instron Corporation of the United States. The results are shown in Table 4.
[0077] Table 4 Tensile breaking force of each material under different printing conditions (N)
[0078]
[0079] The sample strip was observed under a 10x eyepiece and a 5x objective lens using an optical microscope to obtain the true bonding width, and the interlaminar strength was calculated to be tensile breaking force / (true bonding width*speline strip length).
[0080] The actual bonding width of each sample strip obtained under microscope observation is shown in Table 5.
[0081] Table 5 Actual bonding width of each sample under microscope observation (μm)
[0082]
[0083] By comparing the stress at fracture of the samples, taking 20% PBAT as an example ( Figure 2 ) and when the printing layer thickness is 0.2mm ( Figure 3) We can find that the nozzle temperature affects the interlayer adhesion and interlayer strength. As the temperature rises, the stress reaches an extreme value and the curve shows an inverted V shape; the stress reaches a maximum value when the thickness is 0.2mm and the temperature is 250 to 260℃.
[0084] Therefore, in order to determine the bonding strength between layers, the printing conditions were selected with a nozzle temperature of 255°C and a layer thickness of 0.2 mm for calculation.
[0085] The cross section of the slice was observed using an optical microscope. Taking 20% PBAT as an example, the results are as follows: Figure 3 As shown, it is found that the actual interlayer bonding area is smaller than the apparent calculated area, so the actual bonding strength needs to be corrected and calculated. It is also necessary to compare it with the actual tensile strength of the material to obtain a true evaluation of the bonding strength. The results are shown in Table 6.
[0086] Table 6 Maximum tensile strength of each sample under appropriate printing conditions
[0087]
[0088] The strength ratio is the ratio of the interlaminar strength to the intrinsic tensile strength.
[0089] The sample strip was observed under a 10x eyepiece and a 5x objective lens using an optical microscope to obtain the true bonding width, and finally the interlaminar strength = tensile breaking force / (true bonding width*speline length).
[0090] The polycarbonate modified material masterbatch was injection molded into a standard tensile specimen and tested under the same conditions (GB / T 1040-92) to obtain the intrinsic tensile strength.
[0091] We can find that under the optimal printing conditions, the interlayer bonding strength of the three formulations all reached more than 85% of the bulk strength of the consumables, indicating that the 3D printed polycarbonate modified material under this formulation has high interlayer bonding strength.
[0092] [Comparative Example 1]
[0093] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Polybutylene adipate terephthalate (PBAT) is produced by BASF of Germany with the brand name C1200. The two particles were dried in a vacuum oven at 60°C for 5 hours to remove moisture. Then they were mixed in a mixer according to the specific ratio of PC / PBAT of 85 / 15, 80 / 20, and 75 / 25 by mass, and the mixing time was 20 minutes. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are: 210°C, 220°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, and 230°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 70% of the maximum value. The extruder is equipped with a circular die with a diameter of 3 mm. After the sample strip is extruded from the die and air-cooled, it is cut into cylindrical particles with a set diameter of about 3 mm by a pelletizer. The above particles are named as 15% PBAT-NA, 20% PBAT-NA, and 25% PBAT-NA. After being dried in a vacuum oven at 60°C for 4 hours, they are packaged for use.
[0094] The above samples 15% PBAT-NA, 20% PBAT-NA, 25% PBAT-NA were prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the traction speed. The final wire diameter was 1.68-1.76 mm.
[0095] The 3D printing filaments 15% PBAT-NA, 20% PBAT-NA, and 25% PBAT-NA prepared in Comparative Example 1 were 3D printed on a MakerBot Replicator 2X 3D printer. The sheet parameters and printing parameters are as follows: the sheet size is a rectangle of 300mm×50mm×0.5mm, the printing parameters are standard resolution, the nozzle extrusion speed is 90mm / s, the moving speed is 90mm / s, the spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is 255℃, and the base plate temperature is 100℃. Under these conditions, the three samples all obtained regular sheets.
[0096] A tensile specimen with a size of 50 mm × 6 mm was prepared using a cutter and a punching machine. The specimen was placed in a dry environment for later use. The tensile properties were tested using a universal tester (model 3344) produced by Instron, USA. The cross section of the sheet was observed using an optical microscope to obtain the final actual tensile strength. The results are shown in Table 7.
[0097] Table 7 Maximum tensile strength of each sample (nozzle temperature 255°C)
[0098]
[0099] Without adding epoxy polyester chain extender, the color of polycarbonate modified material turns yellow, while the tensile strength is slightly reduced, and the actual strength ratio is also reduced by about 9%, indicating that epoxy polyester chain extender can improve the adhesion between layers.
[0100] [Comparative Example 2]
[0101] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Epoxy polyester chain extender is produced by BASF, Germany, with the brand name ADR-4300. PC particles were dried in a vacuum oven at 60℃ for 5 hours to remove moisture. Then they were mixed in a mixer according to a specific mass ratio of PC / ADR of 100 / 0.5 for 20 minutes. The Eurolab16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are: 240℃, 250℃, 250℃, 260℃, 260℃, 260℃, 260℃, 260℃, 260℃, 260℃ and 260℃, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 70% of the maximum value. The extruder is equipped with a circular die with a diameter of 3 mm. After the sample strip is extruded from the die and air-cooled, it is cut into cylindrical particles with a set diameter of about 3 mm by a pelletizer. The above particles are named PC-ADR, and then they are dried in a vacuum drying oven at 60°C for 4 hours and then packaged for use.
[0102] The above samples were prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the pulling speed. The final wire diameter was 1.67-1.75 mm.
[0103] The 3D printing filament PC-ADR prepared in Comparative Example 2 was 3D printed on a MakerBot Replicator 2X 3D printer. The sheet parameters and printing parameters are as follows: the sheet size is a rectangle of 300mm×50mm×0.5mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, moving speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is 255℃, and the base plate temperature is 100℃. Under these conditions, the sheet printing of PC-ADR failed. When the printing height reached 10mm, interlayer tearing occurred and the sheet could not be successfully printed. The possible reason is that the glass transition temperature is high and the fluidity is poor, and the layers cannot be firmly bonded to achieve shaping.
Claims
1. A polycarbonate modified material for 3D printing, obtained by blending raw materials comprising the following components, measured in parts by weight: (1) 60 to 90 parts of polycarbonate; (2) 10 to 40 parts of aliphatic aromatic copolyester; (3) 0.1 to 1 part of epoxy polyester chain extender; The epoxy polyester chain extender is an acrylic acid and styrene copolymer or a styrene-methacrylate glycidyl copolymer containing 5 to 9 epoxy groups, and the weight average molecular weight of the epoxy polyester chain extender is 4000 to 6000; the interlayer strength of the 3D printed sample strip of the polycarbonate modified material reaches more than 85% of the intrinsic tensile strength of the material; The test method of interlaminar strength includes the following steps: The sheets printed from the polycarbonate modified material are made into splines, the tensile breaking force is tested, and then the actual bonding width of the sheets is measured. The interlayer strength is calculated according to the formula: interlayer strength = tensile breaking force / (actual bonding width*spline length).
2. The polycarbonate modified material for 3D printing according to claim 1, characterized in that The product is obtained by blending the following raw materials, in parts by weight: (1) 65 to 90 parts of polycarbonate; (2) 10 to 35 parts of aliphatic aromatic copolyester; (3) 0.2 to 0.6 parts of epoxy polyester chain extender.
3. The polycarbonate modified material for 3D printing according to claim 1, characterized in that: The polycarbonate is at least one of aliphatic polycarbonate, alicyclic polycarbonate and aromatic polycarbonate.
4. The polycarbonate modified material for 3D printing according to claim 3, characterized in that The polycarbonate is an aromatic polycarbonate.
5. The polycarbonate modified material for 3D printing according to claim 4, characterized in that The polycarbonate is bisphenol A type polycarbonate.
6. The polycarbonate modified material for 3D printing according to claim 1, characterized in that: The molecular chain segments of the aliphatic aromatic copolyester contain one or more aliphatic diol units, at least one of aliphatic diacid or aliphatic diacid anhydride, aliphatic diacyl halide, and aliphatic diacyl ester units, and at least one of aromatic diacid or aromatic diacid anhydride, aromatic diacyl halide, and aromatic diacyl ester units.
7. The polycarbonate modified material for 3D printing according to claim 6, characterized in that: The aliphatic aromatic copolyester is polyethylene terephthalate-co-oxalate, polyethylene terephthalate-co-malonate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-suberate, poly(propylene terephthalate-co-oxalate), poly(propylene terephthalate-co-malonate), poly(propylene terephthalate-co-succinate), poly(propylene terephthalate-co-glutarate), poly(propylene terephthalate-co-adipate), poly(propylene terephthalate-co-suberate), poly(propylene terephthalate-co-oxalate). -co-propylene sebacate, polybutylene terephthalate-co-oxalate, polybutylene terephthalate-co-malonate, polybutylene terephthalate-co-succinate, polybutylene terephthalate-co-glutarate, polybutylene terephthalate-co-adipate, polybutylene terephthalate-co-suberate, polyhexylene terephthalate-co-oxalate, polyhexylene terephthalate-co-malonate, polyhexylene terephthalate-co-succinate, polyhexylene terephthalate-co-glutarate, polyhexylene terephthalate-co-adipate, and polyhexylene terephthalate-co-suberate.
8. A method for preparing a polycarbonate modified material for 3D printing according to any one of claims 1 to 7, comprising the following steps: The components including the polycarbonate, aliphatic aromatic copolyester and epoxy polyester chain extender are blended and extruded to obtain the polycarbonate modified material.
9. The method for preparing a polycarbonate modified material according to claim 8, characterized in that: The extrusion temperature is 210-250°C, and the rotation speed is 50-150rpm.
10. A 3D printing filament prepared from the polycarbonate modified material for 3D printing according to any one of claims 1 to 7.
11. A method for preparing a 3D printing filament according to claim 10, comprising continuously melt-extruding the polycarbonate modified material and obtaining the 3D printing filament by oriented drawing.
12. The method for preparing a 3D printing thread according to claim 11, characterized in that: The extrusion temperature is 210-250°C and the rotation speed is 12.0-14.0 rpm; and / or, The traction frequency is 2.5~3.5.
Citation Information
Patent Citations
Polycarbonate modified material for 3D printing, printing wire, and preparation methods of polycarbonate modified material and printing wire
CN109666276A
Cited By
A high hardness polycarbonate material performance test system
CN120404662B